Seinfeld. Season 5 [videorecording (DVD)] - Cherones, Tom; Cherones, Tom; Seinfeld, Jerry; Seinfeld, Jerry; Seinfeld, Jerry; Seinfeld, Jerry; Louis-Dreyfus, Julia; Richards, Michael, 1950 July 14- (Sony Pictures Home Entertainment, 2012)
Follows the lives of stand-up comedian Jerry and his friends in New York City.